A plastid phylogeny of the African rattans (Ancistrophyllinae, Arecaceae) - (:unkn) unknown (My University, 2014)
Over one third of African palms are rattans, e.g. climbing palms. The subtribe Ancistrophyllinae (subfamily Calamoideae) contains most of these with 21 species represented by three genera: Eremospatha, Laccosperma, and Oncocalamus. African rattans are mainly restricted to the tropical rain forests of Central and West Africa and play an important role in the local economy thanks to their use in furniture making. Here, we present a species level phylogeny of the Ancistrophyllinae based on four plastid intergenic spacers (psbA-trnH, psbZ-trnfM, atpI-atpH, and rps3-rpl16) sequenced for 80% of the species found in the subtribe (17/21). Data were analyzed using maximum parsimony, maximum likelihood, and Bayesian inference methods. Our results show that subtribe Ancistrophyllinae is strongly supported as monophyletic, as are the three genera. However, relationships among the genera remain unresolved. Our analyses provide details on the relationships among species within Eremospatha and Laccosperma, but not in Oncocalamus. The species E. cabrae and E. dransfieldii were recovered with strong support as sister, together forming a highly divergent clade sister to the rest of the genus. The four plastid markers used here provide useful levels of resolution and could be considered in other species-level analyses in palms.
Keywords: African Research